Psikoedukasi Work Life Balance Pada Karyawan PT. Sinar Sosro Kantor Penjualan Wilayah Kalimantan Sulawesi - Resekiani Mas Bakar; Afifah Aprillah; Muh. Alif Wirawan Natsir (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2024)
One of the challenges for workers or employees is balancing time for work with their personal life, which is commonly called work life balance. The aim of providing work life balance psychoeducation in this social service is to provide an understanding of the importance of work life balance to PT. Sinar Sosro Kantor Penjualan Wilayah Kalimantan Sulawesi employees. The method uses intervention in the form of psychoeducation including psychoeducational preparation (conducting FGDs and surveys), implementing psychoeducation, administering pre-tests and post-tests. The implementation of work life balance psychoeducation was attended by 32 participants from PT. Sinar Sosro Kantor Penjualan Wilayah Kalimantan Sulawesi employees whose work placement is at the Kantor Penjualan Wilayah office. The results of this service show that the work life balance psychoeducation activities carried out can provide employees with an understanding of the importance of work life balance itself. This understanding includes what work life balance is, the concept of work life balance, factors that influence work life balance, signs of poor work life balance, and ideal work life balance.